1D.06: LONGITUDINAL EVALUATION OF CARDIOVASCULAR RISK AFTER PEDIATRIC KIDNEY TRANSPLANTATION. (June 2015) - Schmidt, B.; Thurn-Valsassina, D.; Duzowa, A.; Soezeri, B.; Bayazit, A.; Caliskan, S.; Querfeld, U.; Azukaitis, K.; Wuehl, U.; Schäfer, F.; Melk, A.
Abstract : Objective: Children with chronic kidney disease (CKD) carry an increased cardiovascular risk. Cardiovascular death is the second leading cause of death in children after renal transplantation. The 4C-T (Cardiovascular Comorbidity in Children with CKD and Transplantation) study evaluates cardiovascular target organ damage longitudinally in children prior to and after renal transplantation. Design and method: The multicenter, prospective, observational 4C study enrolled 736 children aged 6 to 17 years with estimated GFR <40 ml/min/1.73 m2 at 55 Pediatric Nephrology centres from 12 European countries. Of these, 226 have started renal replacement therapy (RRT) and entered the 4C-T sub-study. At annual study visits, the morphology and function of the heart and large arteries were monitored by noninvasive methods. Results: 176 of the 226 patients on RRT had at least one visit after RRT start and were included in this analysis. 70 patients had started dialysis and 106 received a transplant. 62% of the patients were transplanted pre-emptively. Overall patients carried a higher cardiovascular risk compared to the age-matched general population as documented by elevated age-adjusted aortic pulse wave velocity (PWV) and carotid intima-media thickness (IMT). Factors determining PWV, IMT and left ventricular mass index (LVMI) were analysed using mixed longitudinal modelling (table). Figure. No caption available. Conclusions: Our data is consistent with the hypothesis that transplantation lowers cardiovascular risk. Mixed modeling allowed to decipher the positive effect of transplantation from interfering cardiovascular risk factors such as hypertension, hypercholesterolemia and PTH.